Increased Intestinal Peristaltis after Sectio Caesarea with Early Mobilization - Abdul Ghofur; Eko Suryani; Nunuk Sri Purwanti; Fauhatun Fadhila; Sujiyatini Sujiyatini (Universitas Aisyah Pringsewu, 2022)
The process does not always run as it should or normally so it will require an operation (sectio caesarea) to be able to give birth to a baby with the aim of the safety of the mother and the baby itself. Surgery that is less risky and shorter can be done by giving spinal anesthesia. This technique of giving anesthesia is easier with only one time, shorter and simpler, faster and safer and more satisfying action for the mother in labor. The importance of early mobilization in laboring mothers to prevent abdominal muscle stiffness and will restore intestinal peristalsis. Because spinal anesthesia can affect the extremities and digestive tract. The purpose of this study was to determine the effect of early mobilization on the recovery of intestinal peristalsis post sectio caesarea with spinal anesthesia in Bendan Pekalongan Hospital. This research method is quasi-experimental research with one control group, each group has 27 respondents. The intervention group was mobilized early from the hospital plus the investigator and the control group were mobilized from the hospital. In this study using a cone sampling technique. By testing the influence of Wilcoxon then with the Mann-Whitney difference test. The results showed that there was an effect of early mobilization on the recovery of intestinal peristalsis post sectio caesarea with spinal. Abstrak: Proses persalinan yang tidak selalu berjalan seperti layaknya atau normal sehingga akan memerlukan salah satu tindakan tindakan operasi (sectio caesarea) untuk dapat melahirkan bayi dengan tujuan demi keselamatan ibu dan bayi itu sendiri. Tindakan operasi yang tidak banyak memberikan risiko dan lebih singkat dapat dilakukan dengan pemberian anestasi spinal. Teknik emberian anestasi ini lebih mudah dengan hanya satu kali suntikan, lebih singkat dan sederhana, onset tindakan lebih cepat dan lebih aman dan memuaskan bagi ibu bersalin. Pentingnya mobilisasi dini pada ibu bersalin untuk mencegah kekakuan otot perut dan akan mengembalikan kerja peristaltik usus. Karena anastesi spinal dapat mempengaruhi ekstrimitas dan saluran pencernaan. Tujuan penelitian ini adalah untuk mengetahui pengaruh mobilisasi dini terhadap pemulihan peristaltik usus post sectio caesarea dengan anestesi spinal di RSUD Bendan Pekalongan. Metode penelitian ini adalah penelitian quasi eksperimen dengan satu kelompok kontrol setiap kelompok ada 27 responden. Kelompok intervensi dimobilisasi awal dari rumah sakit ditambah peneliti dan kelompok kontrol dimobilisasi dari rumah sakit. Dalam penelitian ini menggunakan teknik pengambilan sampel kerucut. Dengan menguji pengaruh Wilcoxon kemudian dengan uji beda Mann-Whitney. Hasil penelitian menunjukkan bahwa ada pengaruh mobilisasi dini terhadap pemulihan peristaltik usus post sectio caesarea dengan spinal